Effect of diet containing palm kernel cake and coconut meal cake on growth performance and carcass quality of free-range chicken in Malaysia - M. Mohd Shahmi Hakimi,; Z. Alias,; M.M. Rahman,; W.E. Wan Khadijah,; R.B. Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Significant increase in feed cost has forced many farmers to identify new alternative sources for free-range chicken diet by using local ingredients to replace imported feeds. This study aim was to evaluate the effect of age and diet containing palm kernel cake (PKC) and coconut meal cake (CMC) on feed intake, growth and carcass quality of free-range chickens in Malaysia. Two hundred crossbred free-range chickens were reared from day old to 12 Weeks of age. At 3 Weeks of age, chickens were divided into 2 dietary treatment groups: Commercial finisher diet (CFD) and formulated finisher diet (FFD) containing CMC and PKC, whereby the body weight and feed intake were measured weekly until the end of the study. The chickens were slaughtered at 9 and 12 Weeks of age. Most data showed no significant difference on growth performance between diets. Male CFD showed higher growth rate than the male FFD diet, while no significant difference was observed on growth rate of female chicken for both diets. Despite that, FFD fed chickens showed no significant different between CFD chickens in term of meat to bone ratio at 12th Week of age, indicating that FFD could result in production meat as good as CFD chickens and produce low undesirable products. In conclusion, CMC and PKC have the potential to be used in FFD as an alternative to CFD for free range chickens.